Comparative detection of goat's milk casein through various enzyme-linked immunosorbent assay (ELISA) approaches using caprine alpha-S1 casein peptides and bovine casein polyclonal antibodies - Mohd Samsudin, Nurul Izza Nabilah; Sukor, Rashidah; Mohsin, Aliah Zannierah; Saari, Nazamid (John Wiley and Sons, 2024)
Casein causes allergic reactions in cow's milk protein allergy (CMPA) individuals. Casein can cross-react with cows and goats. Hence, a rapid and highly specific technique is required for its detection. The study aims to evaluate and optimise multiple Enzyme-Linked Immunosorbent Assay (ELISA) approaches for the detection of casein isolated from goat's milk. The study utilised and optimised various ELISA approaches, including direct, indirect and sandwich with various antibodies. Several parameters of ELISA including pre-treatments of casein, blocking reagent, concentrations of antibodies and background signal were evaluated. The results showed that sandwich ELISA revealed a good signal-to-noise ratio at 1 mg mL−1. Indirect ELISA showed a higher signal-to-noise ratio without any heat treatment in comparison to the direct ELISA despite utilising an equivalent concentration (i.e., 10 μg mL−1) of goat's milk casein. The findings provide a theoretical foundation for obtaining a high signal-to-noise ratio for antigenicity studies of goat's milk casein to minimise its immunological response.